Effect of Hydrophilic Monomer Distribution on Self‐Assembly of a pH‐Responsive Copolymer: Spheres, Worms and Vesicles from a Single Copolymer Composition. Issue 9 (9th November 2020) - Zhang, Junliang; Farias‐Mancilla, Barbara; Kulai, Ihor; Hoeppener, Stephanie; Lonetti, Barbara; Prévost, Sylvain; Ulbrich, Jens; Destarac, Mathias; Colombani, Olivier; Schubert, Ulrich S.; Guerrero‐Sanchez, Carlos; Harrisson, Simon
Abstract: A series of copolymers containing 50 mol % acrylic acid (AA) and 50 mol % butyl acrylate (BA) but with differing composition profiles ranging from an AA‐BA diblock copolymer to a linear gradient poly(AA‐ grad ‐BA) copolymer were synthesized and their pH‐responsive self‐assembly behavior was investigated. While assemblies of the AA‐BA diblock copolymer were kinetically frozen, the gradient‐like compositions underwent reversible changes in size and morphology in response to changes in pH. In particular, a diblock copolymer consisting of two random copolymer segments of equal length (16 mol % and 84 mol % AA content, respectively) formed spherical micelles at pH >5, a mix of spherical and wormlike micelles at pH 5 and vesicles at pH 4. These assemblies were characterized by dynamic light scattering, cryo‐transmission electron microscopy and small angle neutron scattering. Abstract : Copolymers of acrylic acid (AA) and butyl acrylate (BA) with constant overall composition (1:1 AA:BA) and controlled composition profiles (gradient, asymmetric diblock and asymmetric triblock) show dynamic pH‐responsive self‐assembly behavior, with reversible changes in size and formation of sphere, worm and vesicle morphologies, in contrast to the frozen micelles formed by poly(AA‐ block ‐BA) block copolymers.